2015
DOI: 10.3390/ijms160922856
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PTP1B O-GlcNAcylation in Hepatic Insulin Resistance

Abstract: Protein tyrosine phosphatase 1B (PTP1B), which can directly dephosphorylate both the insulin receptor and insulin receptor substrate 1 (IRS-1), thereby terminating insulin signaling, reportedly plays an important role in insulin resistance. Accumulating evidence has demonstrated that O-GlcNAc modification regulates functions of several important components of insulin signal pathway. In this study, we identified that PTP1B is modified by O-GlcNAcylation at three O-GlcNAc sites (Ser104, Ser201, and Ser386). Palm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The mechanism by which O-GlcNAc-inducing treatment inhibits IGF-1-induced PTP1B activity is unclear at the present time. A previous study showed that in liver cells, PTP1B could be O-GlcNAcylated by high glucose and/or by inhibition of OGA with PUGNAc, associated with decreased insulin-induced Akt phosphorylation 61 . However, we have evaluated the effect of TG + GlcN treatment on PTP1B O-GlcNAcylation and observed that no O-GlcNAc signal above background could be detected using RL2 antibody (Suppl.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism by which O-GlcNAc-inducing treatment inhibits IGF-1-induced PTP1B activity is unclear at the present time. A previous study showed that in liver cells, PTP1B could be O-GlcNAcylated by high glucose and/or by inhibition of OGA with PUGNAc, associated with decreased insulin-induced Akt phosphorylation 61 . However, we have evaluated the effect of TG + GlcN treatment on PTP1B O-GlcNAcylation and observed that no O-GlcNAc signal above background could be detected using RL2 antibody (Suppl.…”
Section: Discussionmentioning
confidence: 96%
“…O-GlcNAcylation of protein tyrosine phosphatase 1B (PTP1B) at S104, S201, and S386 inhibits PTP1B activity, which leads to an increase in AKT and GSK3β activity and therefore insulin response in HepG2 cells. 120 Human small CTD phosphatase 1 (hSCP1) was identified as O-GlcNAc modified by Western blot, and its glycosite at S41 was confirmed by Q-TOF MS and site-directed mutagenesis. 121 Additionally, the phosphatase myosin phosphatase target subunit 1 (MYPT1) may regulate the substrate specificity of OGT.…”
Section: Phosphatasesmentioning
confidence: 99%
“…Despite the fact that DC is associated with a state of insulin resistance, few studies have highlighted the effect of the HBP on insulin resistance. Whereas, O-GlcNAcylation of several insulin-signaling key players (such as AKT, PT1B, and PDK1) has been shown to be associated with insulin resistance in the liver ( 90 93 ), the effect of the HBP on insulin signaling in the heart has not been adequately addressed. Recently, we reported that FOXO1 was O-GlcNAcylated in the heart of lipodystrophic diabetic mice and that SGLT2i treatment reversed this increase ( 44 ).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%